Exploring Critical Literacy Activities to Promote Students' Adoption of Critical Stances Toward Texts in an EFL Class (2020)
ABSTRACT: This paper reports a teaching and action research experience focused on promoting students’ adoption of critical stances toward texts through the implementation of a cycle of Critical Literacy activities. The project was developed with a group of 39 9th grade students in an EFL class at a public institution in the east of Antioquia, Colombia. As results suggest, most students adopted critical stances toward texts throughout the development of actions, which consisted in the analysis of texts about issues of power, the creation of alternative texts, and the planning of actions in favor of equity. In consequence, most students consciously engaged toward texts, entertained alternate ways of being, took responsibility to inquire, and showed reflection about different patterns of oppression.